STUDY ON EMOTIONAL INTELLIGENCE FOR EMPLOYEE WELL-BEING: RETAINING HIGH-PERFORMING WOMEN IN LEADERSHIP (CAHIERS MAGELLANES-NS, 2024)
This study embarks on an exploration into how Emotional Intelligence (EI) can be a pivotal factor in enhancing employee well-being, with a specific focus on retaining high-performing women in leadership roles within Delhi's Information Technology (IT) sector. Given the sector's dynamic landscape, marked by rapid technological progress and stiff market competition, the workforce, especially women in leadership, navigates a complex array of professional achievements alongside societal and familial expectations. By leveraging a mixed-methods approach, integrating quantitative data from structured questionnaires with qualitative insights, the research illuminates the direct and indirect influences of EI on job satisfaction and overall well-being among female IT professionals. It uncovers the dual challenges of the 'double burden' syndrome and the glass ceiling effect as critical barriers to career advancement and personal fulfillment. Grounded in Employee Well-being Theory, Leadership, and Gender Theory, and contextualized within the unique cultural and organizational fabric of Delhi's IT industry, this study proposes a set of innovative, EI-centric strategies aimed at fostering workplace flexibility, comprehensive well-being programs, and gender-sensitive policies. The ultimate goal is to pave the way for more inclusive and supportive work environments, thus contributing significantly to the discourse on gender-specific challenges and strategies for empowerment in the IT sector.